Deposit Guarantee Systems in Russia and the USA - Florczak, Tomasz; Paduszyńska, Marta (Journal of Finance and Financial Law, 2020)
The purpose of the article/hypothesis: The purpose of the article was to indicate the results of operations of deposit guarantee systems in Russia and the USA. The research hypothesis was that the deposit guarantee system in Russia during the 2004–2018 research period was more heavily burdened with guarantee activities. Methodology: The article is largely based on a review, analysis and synthesis selected publications and available statistical data, and also expanded on the conclusions of the authors and the results of research in the discussed area. Results of the research: The results of the conducted research indicate a high burden on the institution guaranteeing deposits in Russia (DIS). This is primarily the result of actions aimed at stabilizing the Russian banking sector.